Alkaline dissolution potential of aluminosilicate minerals for the geosynthesis of mine paste backfill. (September 2020) - Ouffa, Noureddine; Benzaazoua, Mostafa; Belem, Tikou; Trauchessec, Romain; Lecomte, André
Abstract: Geopolymers are aluminosilicate materials geosynthesized by alkaline activation of aluminosilicate minerals and/or industrial byproducts. This study seeks to understand the geopolymerization processes that could occur in Al/Si-rich mine tailings for producing geopolymer paste backfills (GPB). To do so, the alkaline dissolution of fifteen, commonly encountered pure aluminosilicate minerals was investigated. Different relationships of alkaline dissolution extents were investigated. This revealed that the dissolution extent of the involved mineral depends primarily on its crystallization conditions as well as its chemical composition. Preliminary geopolymerization tests were conducted on conventional mine tailings from the Abitibi region of Quebec, Canada. These tests suggested that GPBs could be obtained with appreciable compressive strengths (UCS) (from 79 to 318 kPa) at low alkalinities ([NaOH] ≤ 1 mol/L) in the long term (beyond 28 days). However, in the short term (≤ 7 days), the use of more soluble aluminosilicate materials is mandatory to ensuring the required target UCS for a GPB.